A mechanical model of fatigue crack propagation. Report 1 - Karzov, G.P.; Leonov, V.P; Margolin, B.Z. (Проблемы прочности, 1985)
The proposed solution of the cyclic elastoplastic problem of the stress--strain state at the crack tip can be used to determine all the necessary parameters taking into account the effect of the triaxial stress state in calculating the fatigue crack propagation rate on the basis of the proposed strain criteria of fracture.